Institutional arrangement for mitigating and adapting to climate change-related flood risk in Greater Accra Metropolitan Area (GAMA) - Alex Barimah Owusu; Kofi Adu-Boahen; Ishmael Yaw Dadson (City and Environment Interactions, 2024)
Episodic floods, attributable primarily to climate change, global warming, and sea level rise, have worsened and continue to be a significant threat to life. Building resilience and improving the adaptive capacities of communities under threat will require institutional and cross-agency collaboration. This paper assessed institutional arrangements for mitigating and adapting to climate change-related flood risk in GAMA, Ghana. Using a descriptive cross-sectional survey, the study collected and analysed data from 65 private businesses and governmental, community, and civil society organisations to assess how institutions collaborate in preparing and adapting to flood risks in the study area. The study finds that frequent flooding, destruction of property and lives, and regular community agitations have triggered high-level consciousness, institutional arrangements, and collaboration within and among communities to build capacity and resilience. In addition, organisations have been educating indigenes on flood preparedness, providing relief items to support flood victims, and conducting training and research. Organisations have also supported communities in developing sandbags, planning sea defence mechanisms, providing rescue and evacuation assistance, providing transportation and logistics, and relocating stranded flood victims. Despite these efforts, the lack of adequate funding and logistics, coupled with the absence of proper consultation and involvement of most organisations in making national-level decisions on climate change and flood-related issues, have rendered flood management efforts less effective. This paper makes the case that proactive and collaborative flood responses should replace reactive and individual approaches to improve flood control efficacy and minimise casualties and property losses.